CLIMATE CHANGE RISKS AND TOURISM IN SOUTH AFRICA: PROJECTIONS AND POLICY - Wayde R. PANDY; Christian M. ROGERSON (Geo Journal of Tourism and Geosites, 2021)
The challenge of climate change and tourism is an evolving international knowledge domain. South Africa is one of the most vulnerable countries with respect to projected climate change. For the national tourism economy climate change is a significant topic of concern. The objectives in this article are to present climate change projections and potential impacts for South Africa‟s tourism economy and to critically analyse the policy landscape concerning national government‟s response to climate change as a whole and more specifically in relation to the tourism sector. It is shown key tourism assets of South Africa are at risk from the advance of climate change. The analysis discloses that the South African government has supported international efforts and obligations to address the challenge of climate change, commitments which have influenced policy development regarding tourism. Nevertheless, policy development towards climate change and tourism has not progressed greatly over the past decade. Arguably, this is an outcome of the overwhelming concentration in recent government tourism policy in South Africa towards issues of inclusivity and transformation.